PERIODICATION OF MEDIEVAL HISTORY: PROBLEMS AND SOLUTIONS (in the case of Asian and African countries). (UBS Scientific Bulletin, 2024)
The article provides brief information about the periodization of the medieval part of world history, the medieval states of Asia and Africa, their political, social, economic and cultural life.